PENGARUH PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA MUHAMMADIYAH MASBAGIK TAHUN PELAJARAN 2012/2013 - L Muh. Rispan Sugi Saputra (Universitas Pendidikan Mandalika, 2013)
This study aims to determine the effect of cooperative learning 'STAD type' on physics learning outcomes of students class X SMA Muhammadiyah Masbagik Academic Year 2012/2013. This research is quasi experiment and its population is all class X high school student. The sample of research is 2 classes that have been determined with purposive sampling technique, that is 25 people from class X-1 as experiment class and 24 person from class X-2 as control. The experimental class used the STAD-type cooperative model and control class using the conventional learning model. The normalized gain-averaged scores for the experimental class were 0.45 (medium category) and 0.33 (medium category) for the control class. We conclude that the experiment class is better than the control class. Based on hypothesis test result t-test = 2.12> t-table = 2.012. That is, there is a significant influence of the STAD model on learning outcomes rather than conventional.